1993
DOI: 10.1007/bf02072035
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen induces hepatocellular carcinoma in rat liver: A 1-year study with two antiestrogens

Abstract: The effects of equimolar doses of the triphenylethylene antiestrogens tamoxifen and toremifene on female Sprague-Dawley rat liver were studied in a 52-week toxicity study which included a 13-week recovery period. Liver tumors were found in four out of five rats at the highest dose level of tamoxifen (45 mg/kg per day) after 52 weeks of dosing, and these appeared to be hepatocellular carcinomas in three rats. After the 13-week recovery period all surviving rats in the highest tamoxifen dose group had large live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(36 citation statements)
references
References 4 publications
0
34
0
2
Order By: Relevance
“…initiation of tumours or mutagenesis of p53 tumour suppressor gene (Styles et al, 1994;Vancutsem et al, 1994). As TAM induces DNA adducts and is carcinogenic in the rat liver (Han and Liehr, 1992;Hard et al, 1993;Hirsimaki et al, 1993;Montandon et al, 1994), non-hormonal mechanisms might be preferentially related to the initiation of secondary malignancies. The recent report that TAM-treated patients have an increased incidence of gastrointestinal tumours is disconcerting (Rutqvist et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…initiation of tumours or mutagenesis of p53 tumour suppressor gene (Styles et al, 1994;Vancutsem et al, 1994). As TAM induces DNA adducts and is carcinogenic in the rat liver (Han and Liehr, 1992;Hard et al, 1993;Hirsimaki et al, 1993;Montandon et al, 1994), non-hormonal mechanisms might be preferentially related to the initiation of secondary malignancies. The recent report that TAM-treated patients have an increased incidence of gastrointestinal tumours is disconcerting (Rutqvist et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The most common adverse drug reaction consists in climacteric-like symptoms, but the drug has also been reported to generate DNA adducts in human hepatocyte cultures and in rats and Syrian hamsters (Han et al, 1992;White et al, 1992;Hard et al, 1993). TAM is a liver carcinogen in rats (Hirsimaki et al, 1993;Vancutsem et al, 1994) and it increases the risk of endometrial and gastrointestinal cancers in patients (Fisher et al, 1994; De Gregorio et al, 1995;Rutqvist et al, 1995) and increases the number of polyps in the endometrium (Lahti et al, 1993). Clearly, an anti-oestrogen that lacks these carcinogenic characteristics while retaining the beneficial effects of TAM is desirable (Zito, 1994).…”
mentioning
confidence: 99%
“…The finding that tamoxifen at high doses caused liver tumors in rats [61] raised concern that it may be mutagenic in humans. The mechanism of this effect in laboratory animals was believed to be due to DNA adduct formation by metabolites of tamoxifen, although this has more recently been questioned [62] .…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Tamoxifen decreases the incidence of mammary tumors in rodent carcinogenesis studies [Gottardis et al, 1996]. There has been concern that preclinical studies have demonstrated an increased risk of liver tumors in rodent models [Hirsimaki et al, 1993;Williams et al, 1993]; however, there has been no increase in liver cancer in humans [Muhlemann et al, 1994;Wilking et al, 1997]. Adjuvant studies of tamoxifen demonstrate a 30 -50% decrease in the development of contralateral breast cancer in tamoxifen-treated women [EBCTCG, 1998] and tamoxifen is well tolerated with potential beneficial effects on postmenopausal bone mineral density and lipid profiles [Love et al, 1991[Love et al, , 1992[Love et al, , 1994.…”
Section: Randomized Trials Selective Estrogen Receptor Modulators (Sementioning
confidence: 99%